Lens-specific expression of the chloramphenicol acetyltransferase gene promoted by 5' flanking sequences of the murine alpha A-crystallin gene in explanted chicken lens epithelia. - Chepelinsky, A B (1985)
We have developed a system using explanted embryonic chicken lens epithelia to express foreign recombinant genes containing crystallin DNA regulatory sequences introduced by calcium phosphate transfection. Optimal results were obtained with lens epithelia from 14-day embryos transfected 1 day after explantation and assayed 3 days later. When DNA sequences (-364 to +45) of the murine alpha A-crystallin gene were inserted in the pSVO-CAT expression vector of Gorman et al. [Gorman, C. M., Moffat, L. F. & Howard, B. H. (1982) Mol. Cell. Biol. 2, 1044-1051] in the same orientation as in the crystallin gene, they promoted chloramphenicol acetyltransferase (CAT; EC 2.3.1.28) activity in the transfected epithelia. Sequences 87 to 364 base pairs upstream from the murine gene cap site were required for CAT gene expression. These crystallin gene regulatory sequences did not promote CAT expression in primary cultures of embryonic chicken fibroblasts or other nonlens cells. By contrast, the long terminal repeat of Rous sarcoma virus and the early promoter of simian virus 40 promoted CAT activity in lens and nonlens cells. Our experiments thus demonstrate that the explanted embryonic chicken lens epithelium is an advantageous recipient for identifying lens-cell-specific regulatory sequences of crystallin genes and implicate a DNA region upstream of the "TATA box" for regulation of the murine alpha A-crystallin gene. These experiments also suggest that explanted epithelia from other tissues may be useful for studying the expression of foreign genes.